Awareness of urban expansion with ecological balance: exploring Tambun, Perak's sensitive environmental development / Nurul Azmina Husin and Zulkefle Ayob - Husin, Nurul Azmina; Ayob, Zulkefle (2024)
This research endeavours to comprehensively explore the intricate challenge of reconciling urban expansion with the preservation of ecological balance in Tambun, Perak. The accelerated urbanisation driven by economic progress and shifting demographics presents a formidable conundrum, necessitating a harmonious coexistence between urban development and the fragile environment. The principal objective of this study is to investigate the community's awareness and perception of urban expansion's impact on ecological balance, with the overarching goal of fostering sustainable urban development in Tambun, Perak. A questionnaire and field survey of a total of 50 respondents was conducted to evaluate their views regarding the findings, demonstrating that 72% of the participants favoured scale 5, indicating a substantial emphasis on environmental conservation and protection. Furthermore, 18% of the respondents showed support by selecting scale 4, while 8% opted for scale 3. These results underscore a widespread acknowledgement of the importance of environmental conservation and protection within the surveyed population. The high percentage of respondents endorsing the largest scale reflects a collective recognition of the critical role of environmental preservation, emphasising a shared commitment to conserving natural resources and safeguarding ecological balance.